Analysis of intonation - the state of art. - Manjula R (Journal of All India Institute of Speech and Hearing, 1970)
Analysis of Intonation in different Ian- Words uttered with two different pitch patguages has ceased to be of sole interest to an terns indicate two different meanings in a elocutionist. More and more professionals tone language, e.g. Chinese and Thai Ianlike the linguists and phoneticians are in- guages. In Intonation  languages, there curvolved in this task. Study of structures and ring pitch patterns occuron a word or phrase functions of intonation features from the I in- or sentence of varying length e.g. English guistic and acoustic point of view has gained and Kannada. To date, the distinctions momentum in the recent past. Intonation in between Intonation languages and Pitch accent different languages and its variations in languages are not very clear. The accented different contexts are being critically evalu- syllable (syllables assuming prominence in ated by various authorities; principally, the an utterance) may occur in any position of an linguistics and phoneticians (Bolinger, 1972; utterance depending on factors such as the Hadding-Koch & Studdart-Kennedy, 1964; intent of the speaker and the word that has Lehiste & Peterson, 1979;) who have made to be emphasized in an Intonation language, their valuable contribution towards an un- On the other hand, in Pitch accent language understanding of the intonation features.